Self-assembled nanoparticles made of dextrin - Gonçalves, Catarina (2006)
The amphiphilic molecule dextrin-VA-SC16 (dexC16) was produced and studied in this work. DexC16 has a hydrophilic dextrin backbone with grafted acrylate groups (VA), substituted with hydrophobic 1- exadecanethiol (C16). The dextrin degree of substitution with the hydrophobic chains (DSC16, number of alkyl chains per 100 dextrin glucopyranoside residues) may be controlled. Materials with different DSC16 were prepared and characterized using ¹H NMR. DexC16 self assembles in water through association of the hydrophobic alkyl chains, originating hydrogel nanoparticles. The properties of the hydrogel nanoparticle were studied by dynamic light scattering (DLS), fluorescence spectroscopy and atomic force microscopy (AFM).